Circulating current control scheme of modular multilevel converters supplying passive networks under unbalanced load conditions - Zhang, Huaitian (2020)
Load imbalances in the supply of passive loads with modular multilevel converter (MMC)-based medium (MVDC) and high voltage (HVDC) dc-links are inevitable. In such applications, the maximum-allowable voltage ripples and peak arm currents define the operating limits of the MMCs. This paper demonstrates the impact of circulating current control in capacitor voltage ripples of sub-modules and peak arm currents under unbalanced load conditions when supplying passive networks, comparing the effects of three circulating current control methods on internal variables of the MMCs. The efficacy of the circulating current control is validated through real-time digital simulations of an 800 MVA benchmark MMC-based HVDC transmission system.